Kemandirian Dengan Penyesuaian Diri: Study Kasus Mahasiswa Perantauan - Jayanda, Dhiaulhaq; Alfita, Laili (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to determine the corellation between independence and self-adjustment in students from other regions at the University of Medan Area Stambuk 2024. Students from other regions face the challenge of adapting to a new environment that is different from their home region, so independence becomes an important factor in supporting self-adjustment, both emotionally, behaviorally, and value-wise. This study uses a quantitative method with a correlational design. The sample consisted of 35 students from other regions selected using incidental sampling techniques. The research instruments included a Likert-based independence scale and self-adjustment scale. Validity was tested using Pearson Product Moment, while reliability was measured by Cronbach's Alpha. Data analysis was carried out using the Pearson Product Moment correlation test. The results showed a positive and significant relationship between independence and self-adjustment (r = 0.648; p = 0.000). The coefficient of determination (r²) of 0.420 indicates that independence contributes 42% to self-adjustment, while 58% is influenced by other factors. Descriptively, independence is in the moderate category (mean = 79.69) and self-adjustment is also moderate (mean = 90.17). This finding confirms that the higher the independence of students living away from home, the better their ability to adapt to the academic and social environment of their area of residence.